In-line MRI-LINAC depth dose measurements using an in-house plastic scintillation dosimeter. (11th February 2021) - Madden, Levi; Roberts, Natalia; Jelen, Urszula; Dong, Bin; Holloway, Lois; Metcalfe, Peter; Rosenfeld, Anatoly; Li, Enbang
Abstract: Plastic scintillation dosimeters (PSDs) have many properties that make them desirable for relative dosimetry with MRI-LINACs. An in-house PSD, Farmer ionisation chamber and Gafchromic EBT3 film were used to measure central axis percentage depth dose distributions (PDDs) at the Australian MRI-LINAC Mean errors were calculated between each detector's responses, where the in-house PSD was on average within 0.7% of the Farmer chamber and 1.4% of film, while the Farmer chamber and film were on average within 1.1% of each other. However, the PSD systematically over-estimated the dose as depth increased, approaching a maximum overestimation of the order of 3.5% for the smallest field size measured. This trend was statistically insignificant for all other field sizes measured; further investigation is required to determine the source of this effect. The calculated values of mean absolute error are comparable to the those of trusted dosimeters reported in the literature. These mean absolute errors, and the ubiquity of desirable dosimetric qualities inherent to PSDs suggest that PSDs in general are accurate for relative dosimetry with the MRI-LINAC. Further investigation is required into the source of the reported systematic trends dependent on field-size and depth of measurement.